ANALISIS QAWA’ID FIQHIYYAH TERHADAP MASALAH RUJU DAN ILA’ - Zikri, Muhammad; Adly, Muhammad Amar; Firmansyah, Heri (Al-Muqaranah : Jurnal Perbandingan Hukum dan Mazhab, 2025)
This study aims to examine the qawāʿid fiqhiyyah (Islamic legal maxims) related to two significant issues in Islamic family law: rujūʿ (reconciliation) and īlā’ (a husband’s oath of abstinence). Rujūʿ refers to the husband’s right to reconcile with his wife after pronouncing a revocable divorce (ṭalāq rajʿī) during the waiting period (ʿiddah), while īlā’ refers to a husband's oath to abstain from marital relations with his wife for a certain period, which may lead to divorce if it exceeds four months without fay’ (the act of breaking the oath). This research employs a normative legal approach using the statute method, analyzing legal provisions derived from the Qur’an, Hadith, and the views of classical Islamic jurists. The findings indicate that both rujūʿ and īlā’ are firmly rooted in Islamic primary sources and are systematically explained through Islamic legal maxims. The maxim related to rujūʿ asserts that reconciliation is a continuation of a valid marriage contract and does not require a new contract, provided it occurs within the prescribed ʿiddah period. Meanwhile, the maxim concerning īlā’ establishes that the oath of abstinence has a legal limit of four months and is nullified by the husband’s resumption of conjugal relations (fay’). Islam regulates both matters in a balanced manner to preserve marital harmony and protect the rights of women. With proper understanding of the relevant legal maxims, cases involving rujūʿ and īlā’ can be resolved justly, in line with the overarching objectives of Islamic law (maqāṣid al-sharīʿah).Keywords: Qawa’id Fiqhiyyah, Reconciliation, Oath of AbstinenceAbstrakPenelitian ini bertujuan untuk mengkaji kaidah-kaidah fiqhiyyah yang berkaitan dengan dua isu penting dalam hukum keluarga Islam, yaitu rujuk dan ila’. Rujuk merupakan hak suami untuk kembali kepada istrinya yang telah dijatuhi talak raj‘i selama masa iddah, sedangkan ila’ adalah sumpah suami untuk tidak menggauli istrinya dalam jangka waktu tertentu, yang dapat berujung pada perceraian jika melampaui empat bulan tanpa adanya tindakan fay’. Penelitian ini menggunakan pendekatan normatif dengan metode statute approach, yaitu mengkaji ketentuan hukum berdasarkan nash Al-Qur’an, hadis, dan pendapat para ulama fikih. Hasil penelitian menunjukkan bahwa kedua permasalahan ini memiliki dasar hukum yang kuat baik dari Al-Qur’an maupun hadis Nabi ﷺ, serta dijelaskan secara sistematis dalam kaidah-kaidah fiqhiyyah. Kaidah tentang rujuk menegaskan bahwa rujuk merupakan bentuk kelanjutan dari akad nikah yang sah dan tidak memerlukan akad baru, selama dilakukan dalam masa iddah. Sedangkan kaidah tentang ila’ menjelaskan bahwa sumpah untuk tidak menggauli istri memiliki batas maksimal empat bulan, dan dapat gugur dengan tindakan fay’. Islam mengatur keduanya secara proporsional demi menjaga keutuhan rumah tangga dan melindungi hak-hak perempuan. Dengan pemahaman kaidah yang tepat, penyelesaian perkara rujuk dan ila’ dapat diterapkan secara adil, sesuai dengan prinsip maqāṣid al-syarī‘ah.Kata Kunci: Qawāʿid Fiqhiyyah, Rujuk, Ila’